Symbolic Processing Mediates the Relation Between Non-symbolic Processing and Later Arithmetic Performance - Finke, Sabrina; Freudenthaler, H. Harald; Landerl, Karin (Frontiers in Psychology, 2020)
The nature of the relation between nonsymbolic and symbolic magnitude processing in the prediction of arithmetic remains a hotly debated subject. This longitudinal study examined whether the influence of nonsymbolic magnitude processing on arithmetic is mediated by symbolic processing skills. A sample of 130 children with age-adequate (N = 73) or below-average (N = 57) achievement in early arithmetic was followed from the end of Grade 1 (mean age: 86.9 months) through the beginning of Grade 4. Symbolic comparison of one- and two-digit numbers serially mediated the effect of nonsymbolic comparison on later arithmetic. These results support a developmental model in which nonsymbolic processing provides a scaffold for single-digit processing, which in turn influences multi-digit processing and arithmetic. In conclusion, both nonsymbolic and symbolic processing play an important role in the development of arithmetic during primary school and might be valuable long-term indicators for the early identification of children at risk for low achievement in arithmetic.